(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
ThePreparation of nanorod involves simple and novel design of sol-gel process. Further, by using the prepared nanorods, working electrode will be prepared and it will be sensitized with ruthenium dye. A platinum coated FTO electrode will be used as a counter electrode. Dye sensitized solar cell will be assembled by using the working electrode and counter electrode. FE-SEM and UV characteristics have been carried out at 250áµ’C, 350áµ’C&450áµ’C. The size and band gap of nanorod at these temperatures has been found out to be 1Î¼m and 2.95eV, 200nm and 2.86eV, 100nm and 2.79eV respectively. The power conversion efficiency and the fill factor have been obtained as 2.72% and 0.722 respectively.